Facing the challenges of whole-school reform : New American Schools after a decade - Berends, Mark, 1962-; Bodilly, Susan J.; Kirby, Sheila Nataraj, 1946-; New American Schools (Organization) (Santa Monica, Calif. : Rand Education, 2002)
After a decade of studies, this report released in 2002, draws together RAND's research on New American Schools, highlighting the organizations significant contribution to comprehensive school reform and noting the challenges that came with implementing whole-school designs.
Introduction -- The development of New American Schools -- Changes in NAS designs -- Implementation of NAS designs during the scale-up phase -- Implementation of NAS designs in a high-poverty district -- NAS designs and academic achievement -- The future of whole-school designs: conclusions, observations, and policy implications -- Afterword -- Appendix. Methodology for the studies on implementation and performance.
"MR-1498-EDU"--Page 4 of cover
Includes bibliographical references (pages 209-222).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: New American Schools (Organization); New American Schools (Organization); New American Schools; School improvement programs -- United States; Enseignement -- Réforme -- États-Unis.; EDUCATION -- Administration -- General; EDUCATION -- Educational Policy & Reform -- General; School improvement programs; United States; Schulreform; USA; Enseignement -- Réforme -- États-Unis.